COMPARATIVE STUDY OF TITLES IN ENGLISH POP SONGS AND THOSE IN THEIR TRANSLATED VERSIONS BASED ON NEWMARK’S MODEL - Quynh, Doan Thuy (VNU Journal of Foreign Studies; Vol 36 No 5DO - 10.25073/2525-2445/vnufs.4611, 2020)
In this study, we compare and contrast the titles of English pop songs with those of Vietnamese translated versions based on Newmark’s model. 65 titles in the original and 65 titles in the target language were chosen to compare and contrast with the purpose of seeing how many titles are retained and how many titles are novel in terms of content. To reach its aim, the study used two main methods including comparison and description, which were based on Newmark’s model. In addition, statistical and analysis methods were also applied to examining the titles. The research findings showed that in general 51 titles are retained in the target language through 5 translation methods: literal translation, semantic translation, communicative translation, free translation and adaption. 10 titles do not carry any characteristics in comparison with the original. The study also revealed that translators used mainly free translation to convert the titles from English into Vietnamese.